RETRACTION: Rmuš, V. 2017. Constructions of squaring the circle, doubling the cube and angle trisection. Vojnotehnički glasnik/Military Technical Courier, 65(3), pp.617-640 - Editorial Office, Redakcija / (Vojnotehnički glasnik / Military Technical Courier, 2020)
The Editorial Office of the Military Technical Courier is retracting the article titled „Constructions of squaring the circle, doubling the cube and angle trisection“ of the author Veselin M. Rmuš, published in the Military Technical Courier vol. 65, no. 3/2017, pp.617-640 (doi:10.5937/vojtehg65-13404; https://doi.org/10.5937/vojtehg65-13404). The article is retracted because the final version of the article did not take into account the referee’s explicitly stated remark that the article deals with a new approach to solving the problem and not with the final solution to the problem as such a conclusion may be drawn from the published article. The Editorial Office expresses regret and sincere apology to the readers; we considered, with our engineering thinking, that the approximate solutions given in this work can also be scientifically relevant in the mathematical context of this classical, ancient Greek problem, which can by no means be an excuse.